Dietary Habits, Nutritional Knowledge, and Quality of Life Among Patients with Gastrointestinal Cancers: An Exploratory Cross-Sectional Survey - Katarzyna Antosik; Damian Dyńka; Elżbieta Krzęcio-Nieczyporuk; Maja Księżopolska; Milena Kobylińska; Katarzyna Kurowska (Journal of Clinical Medicine, 2026)
Background: Cancer is one of the leading causes of morbidity and mortality worldwide, and epidemiological projections indicate that its incidence will continue to increase. Gastrointestinal cancers are among the most frequently diagnosed malignant neoplasms. Quality of life is a key component of oncology care and is significantly influenced by nutritional status and dietary habits. Methods: The study included 52 adult patients diagnosed with gastrointestinal cancer. Data were collected using an anonymous questionnaire based on the QEB (Questionnaire of Eating Behaviour) and WHOQOL-BREF (World Health Organization Quality of Life—BREF) instruments, supplemented with questions regarding changes in dietary habits and the use of dietary counseling following diagnosis. Nutritional knowledge, dietary habits, and quality of life across four domains (physical, psychological, social, and environmental) were assessed. Statistical analysis was performed using descriptive statistics and appropriate tests of statistical significance. Results: Cancers of the colon and rectum—reported either as unspecified colorectal cancer or as separately specified colon or rectal cancer—together accounted for the largest share of diagnoses (26 diagnoses, representing 44.8% of the 58 total reported diagnoses). Quality-of-life assessment revealed the lowest scores in the physical domain and the highest scores in the social domain. The youngest participants achieved the highest scores in the psychological domain, whereas the lowest scores across all domains were observed among individuals aged over 60 years. Following diagnosis, 63.5% of participants reported reviewing and modifying their dietary habits; however, the majority had not received dietary counseling. Women reported higher fruit and vegetable consumption than men, while higher educational attainment was associated with greater self-assessed nutritional knowledge. Conclusions: Among patients with gastrointestinal cancers surveyed in this study, the physical domain of quality of life had the lowest WHOQOL-BREF score. Most participants reported modifying their dietary habits after diagnosis, although most had not received formal dietary counseling. Higher educational attainment was associated with higher self-assessed nutritional knowledge. Given the small convenience sample and cross-sectional design, these findings should be considered exploratory.